Peran Ombudsman RI Perwakilan Sumatra Barat dalam Meningkatkan Pelayanan Publik di Sumatra Barat - Sandra, Yarekha; Harits. M, Abdul; Syafril, Rizki (PT Maju Malaqbi Makkarana, 2024)
The Ombudsman is an institution that plays an important role in supervising public services and enforcing administrative ethics in various countries. The main objective of the ombudsman is to ensure that citizens' rights are protected from acts of maladministration or abuse of power by government agencies or other public bodies. This institution functions as an intermediary between the community and the government, receiving and following up on public complaints regarding inadequate public services. An effective ombudsman role can increase accountability and transparency in government, improve the quality of public services, and strengthen public trust in public institutions. In the modern era, ombudsmen also play a role in human rights advocacy, consumer protection, and dealing with integrity and anti-corruption issues, making them a vital component in good and democratic governance structures.